DIAGNOSTIC ROLE OF ULTRASONOGRAPHY FOR INTUSSUSCEPTION IN CHILDREN - Azmat Ali; Mashaal Farooq; Javed, Hamza; Shamsullah Burki; Ummar Nasim Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Intussusception is a common cause of bowel obstruction in children, and early diagnosis is crucial to prevent complications. Ultrasonography is widely used to diagnose intussusception, but its validity parameters in children have not been well-established. The objective of this study is to determine the validity parameters of ultrasonography in diagnosing intussusception in children, taking surgical findings as the gold standard. Methods: This cross-sectional validation study was conducted at the diagnostic radiology and surgery departments of Ayub Teaching Hospital, Abbottabad. This study duration spans from September 2022 to December 2023, and 127children of both sex with ages in the range of 3 months to 12 years suspected to have intussusception on ultrasound as per operational definition were included, and patients managed conservatively were excluded. Ultrasound scan was performed with Toshiba Xario-100 machine using high frequency 8.5 MHz probe. All data, including patients’ demographics were recorded on a proforma. Data analysis was conducted using SPSS version 25. Results: The mean age of patients was 6.50±3.38 years. The diagnostic accuracy of ultrasonography was 85.83%, with sensitivity of 82.93%, specificity of 91.11%, positive predictive value (PPV) of 94.44%, and negative predictive value (NPV) of 74.55%. Conclusion: The use of ultrasonography as a first-line diagnostic tool for intussusception in children can help in early diagnosis and prompt management of the condition, which can significantly reduce the risk of complications.